2018
DOI: 10.1371/journal.pone.0195372
|View full text |Cite
|
Sign up to set email alerts
|

“We did not know what was wrong”—Barriers along the care cascade among hospitalized adolescents with HIV in Gaborone, Botswana

Abstract: High mortality among adolescents with HIV reflects delays and failures in the care cascade. We sought to elucidate critical missed opportunities and barriers to care among adolescents hospitalized with HIV at Botswana’s tertiary referral hospital. We enrolled all HIV-infected adolescents (aged 10–19 years) hospitalized with any diagnosis other than pregnancy from July 2015 to January 2016. Medical records were reviewed for clinical variables and past engagement in care. Semi-structured interviews of the adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Risk factors for disengagement from HIV care may be heterogeneous, ranging from housing needs and poverty, to stigma and psychological challenges [4,[6][7][8][9][10]. Adolescents are particularly affected by disclosure issues, stigma, mental health, family-level factors and transitions in care [4,[6][7][8][9][10]. There are limited data regarding factors underlying disengagement for ALHIV [6,7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for disengagement from HIV care may be heterogeneous, ranging from housing needs and poverty, to stigma and psychological challenges [4,[6][7][8][9][10]. Adolescents are particularly affected by disclosure issues, stigma, mental health, family-level factors and transitions in care [4,[6][7][8][9][10]. There are limited data regarding factors underlying disengagement for ALHIV [6,7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents are particularly affected by disclosure issues, stigma, mental health, family-level factors and transitions in care [4,[6][7][8][9][10]. There are limited data regarding factors underlying disengagement for ALHIV [6,7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of adherence in paediatrics are heterogeneous, and, consequently, estimates of adherence may be wide-ranging [36]. Numerous complex barriers to adherence by children and adolescents include family-level factors, socio-economic factors, disclosure issues, stigma, mental health concerns and medication factors [25,[36][37][38][39]. Adherence can be particularly challenging as children reach adolescence and as they transition into adult HIV care services [26,38,40,41].…”
Section: Emerging Hiv Resistance In Paediatricsmentioning
confidence: 99%
“…Numerous complex barriers to adherence by children and adolescents include family-level factors, socio-economic factors, disclosure issues, stigma, mental health concerns and medication factors [25,[36][37][38][39]. Adherence can be particularly challenging as children reach adolescence and as they transition into adult HIV care services [26,38,40,41]. While it is widely recognised that adolescents are at risk of decreased adherence to ART, systematic reviews have demonstrated that current evidence regarding strategies to improve adherence is limited [36,42,43].…”
Section: Emerging Hiv Resistance In Paediatricsmentioning
confidence: 99%
See 1 more Smart Citation